Associations of physical activity and sedentary time with cognitive skills in preschoolers: a longitudinal study from preschool to first grade of school - Kirkke Reisberg; Eva-Maria Riso; Liina Animägi; Jaak Jürimäe (BMC Pediatrics)
Abstract Backround Low physical activity and high sedentary behaviour is a concern already during preschool period with potential impacts on children’s future cognitive health in school. However, longitudinal data regarding the associations of physical activity, sedentary time and cognition at young age are limited, thus the aim of this study was to investigate whether objectively monitored moderate-to-vigorous physical activity (MVPA) and sedentary time at preschool age are related to cognitive skills in the first grade of school among boys and girls. Methods Participants were boys (n = 50, aged 6.6 ± 0.5 years) and girls (n = 41, aged 6.5 ± 0.5 years) from thirteen kindergartens and the same children after entering first grade of school. MVPA and sedentary time were measured by means of accelerometer. Modified Boehm-3 test was used to assess cognitive skills. Results MVPA in preschool was unrelated to perceptual, conceptual or verbal skills in school in boys and girls. In boys, higher sedentary time in preschool was associated with higher conceptual skills (β = 0.461, p = 0.040) in school after adjustment for age, baseline conceptual skills, accelerometer wear time and parental education. Conclusions In conclusion, higher sedentariness in preschool is associated with higher conceptual skills in grade one among boys but not in girls. MVPA in preschool is unrelated to cognitive skills in school among boys and girls. The results indicate that perceptual, conceptual and verbal skills in first grade of school are not affected by MVPA level in preschool neither among boys, nor girls. Regarding conceptual skills in school, boys might benefit from sedentary activities during preschool period.